A Morphological Study On English Compound Words Found In Sport News Of The Jakarta Post - Nashrudin, Ilham (2012)
This research analyzed English compound words that are found in sport news of the Jakarta Post. Compound word is defined as two or more words which are combined into one unit a perceptible lexical meaning. This research analyzed how forms of compound word formed and identifying what kinds of compound word that are found. This research aimed to describe how the English compound word forms in sport news of the Jakarta Post newspaper are formed and to identify the kinds of compound words found in sport news of the Jakarta Post newspaper. This research is descriptive qualitative research. In collecting the data, the writer uses observation documentation method. Techniques of analyzing data are Describing the forms of English compound word by using the theory of word formation and Identifying the kind of English compound word by using dictionary. The data are English compound words found in Sport News of The Jakarta Post that was published during November. After analyzing 33 data of English compound words, the researcher finds that (1) There are eight forms of compound word that are identified as a noun compound word, as follows: Noun + Noun, Adjective + Noun, Verb + Noun, Verb + Adverb, Verb + Preposition, Noun + Adverb, Determiner + Noun and Preposition + Noun. (2) There is only one form of compound word that is identified as Adjective compound word. The form is Adjective + Adjective. (3) There is only one form of compound word that is identified as Verb compound word. The form is Preposition + Verb.